Civic Education In Algerian Secondary School English Language Curriculum: A Neglected Dimension? - Dr. Amina Omrani ,Dr. Souad Benguega (Elementary Education Online, 2024)
After the latest educational reforms, the Algerian educational policy has shifted towards incorporating civic themes in EFL teaching; hence EFL secondary school curriculum was built upon civic education (CE) notions with the aim of preparing students to be effective citizens in their society. Thus, the present paper aims at critically analyzing the status of CE in secondary school EFL curriculum. The paper first provides an overview of EFL secondary school syllabi with focus on CE topics. Second, it discusses the main obstacles that hinder the effective incorporation of CE in EFL context through classroom observation and questionnaires directed to both secondary EFL teachers and students. The gathered data show that EFL Secondary School curriculum is designed with a very solid CE perspective and clear preset civic education goals; however, its integration in secondary school classrooms is far from achieving those goals. Thus a reflection on the ways of incorporating CE within EFL secondary school education is recommended to achieve an effective implementation of CE in EFL teaching.